2005
DOI: 10.1159/000088634
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Association of <i>CDC2</i> with Cerebrospinal Fluid Tau in Alzheimer’s Disease

Abstract: We have recently reported that a polymorphism in the cell division cycle (CDC2) gene, designated Ex6 + 7I/D, is associated with Alzheimer’s disease (AD). The CDC2 gene is located on chromosome 10q21.1 close to the marker D10S1225 linked to AD. Active cdc2 accumulates in neurons containing neurofibrillary tangles (NFT), a process that can precede the formation of NFT. Therefore, CDC2 is a promising candidate susceptibility gene for AD. We investigated the possible effects of the CDC2 polymorphism on cerebrospin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 80 publications
0
6
1
Order By: Relevance
“…CDC2 has been associated with AD and with increased levels of tau in cerebrospinal fluid (Johansson A et al, 2003;Johansson A et al, 2005). However, we were not able to replicate these findings in a previous analysis of our complete dataset (Liang X et al, 2007b).…”
Section: Cluster Subsetscontrasting
confidence: 77%
“…CDC2 has been associated with AD and with increased levels of tau in cerebrospinal fluid (Johansson A et al, 2003;Johansson A et al, 2005). However, we were not able to replicate these findings in a previous analysis of our complete dataset (Liang X et al, 2007b).…”
Section: Cluster Subsetscontrasting
confidence: 77%
“…The selective accumulation of CDC2 in neurons bearing neurofibrillary tangles indicates that a mitotic posttranslational mechanism might contribute to the paired helical filament-tau formation in AD [24] . Johansson et al [25] reported that an insertion/ deletion polymorphism influences total tau protein levels in the cerebrospinal fluid using analysis of continuous traits.…”
Section: Discussionmentioning
confidence: 99%
“…Johansson et al [25] sequenced all coding exons, flanking intronic sequences and the promoter region in 10 AD cases and 10 controls and found three polymorphisms [EX6 + 7I/D (rs3212319), rs2456777 and rs2456778], all within 74 bp of each other. We genotyped these three SNPs and three additional SNPs to cover the region.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have found increased levels of Cdk4 in ischemic brain tissue and mouse models of ALS,89, 90 increased levels of Cdk2 and Cdk4 in postmortem brain samples from AD patients,91 and increased Cdk5 activity in MPTP models of PD 92. Furthermore, genetic studies have linked certain polymorphisms of Cdk1 with increased susceptibility to Alzheimer’s disease 93, 94. As mentioned above, Cdk1 can phosphorylate Drp1, increase its activity and stimulate mitochondrial fragmentation 46.…”
Section: Mitochondrial Fission and Sporadic Neurodegenerative Diseasementioning
confidence: 97%